Different Response of Carbonyl Carotenoids to Solvent Proticity Helps To Estimate Structure of the Unknown Carotenoid from Chromera velia - Keşan, Gürkan; Durchan, Milan; Tichý, Josef; Minofar, Babak; Kuznetsova, Valentyna; Fuciman, Marcel; Šlouf, Václav; Parlak, Cemal; Polívka, Tomáš (The journal of physical chemistry. B, 2015)
In order to estimate the possible structure of the unknown carbonyl carotenoid related to isofucoxanthin from Chromera velia denoted as isofucoxanthin-like carotenoid (Ifx-l), we employed steady-state and ultrafast time-resolved spectroscopic techniques to investigate spectroscopic properties of Ifx-l in various solvents. The results were compared with those measured for related carotenoids with known structure: fucoxanthin (Fx) and isofucoxanthin (Ifx). The experimental data were complemented by quantum chemistry calculations and molecular modeling. The data show that Ifx-l must have longer effective conjugation length than Ifx. Yet, the magnitude of polarity-dependent changes in Ifx-l is larger than for Ifx, suggesting significant differences in structure of these two carotenoids. The most interesting spectroscopic feature of Ifx-l is its response to solvent proticity. The transient absorption data show that (1) the magnitude of the ICT-like band of Ifx-l in acetonitrile is larger than in methanol and (2) the S1/ICT lifetime of Ifx-l in acetonitrile, 4 ps, is markedly shorter than in methanol (10 ps). This is opposite behavior than for Fx and Ifx whose S1/ICT lifetimes are always shorter in protic solvent methanol (20 and 13 ps) than in aprotic acetonitrile (30 and 17 ps). Comparison with other carbonyl carotenoids reported earlier showed that proticity response of Ifx-l is consistent with presence of a conjugated lactone ring. Combining the experimental data and quantum chemistry calculations, we estimated a possible structure of Ifx-l.
Keywords: Carotenoids; Solvents; karotenoidy; Alveolata; rozpouštědla